Translational control of autophagy rejuvenates immune responses - Zhang, H (2018)
As our body's guardian, the immune system maintains systemic health through removal of pathogens, damage and cancer. Ageing of the immune system is associated with compromised immune responses as well as decreased tumour surveillance and is therefore a key risk factor for major diseases in the elderly. Adaptive immune responses are mediated by T and B lymphocytes, and failure in adaptive immunity is a particular hallmark of the ageing organism. Here we show that autophagy is impaired in aged murine B lymphocytes, and loss of autophagy causes severely reduced B cell responses. Our data demonstrate that B cell senescence can be reversed in an autophagy-dependent manner by spermidine, a naturally occurring polyamine metabolite. Mechanistically, our study reveals that the translation factor eIF5A, that requires spermidine for its activation, regulates the expression of the master autophagy/lysosomal transcription factor TFEB. Importantly, we show in humans that spermidine, eIF5A and TFEB levels decrease with age and may serve as ageing biomarkers. Taken together our results indicate that the translational control of autophagy by eIF5A is dysregulated with ageing, and identify a novel pathway with therapeutic implications.